Direction of arrival estimation with a sparse uniform array of orthogonally oriented and spatially separated dipole‐triads. Issue 8 (1st October 2014) - Zheng, Guimei; Wu, Bo; Ma, Yan; Chen, Baixiao
Abstract : The problem of multiple incident signals' direction of arrival (DOA) estimation for spatially separated polarisation sensitive array (SS‐PSA) is studied. The proposed SS‐PSA is a sparse uniform array with orthogonally oriented and spatially separated dipole‐triads. The proposed array can reduce the array mutual coupling by using the spatially separated polarised antenna instead of conventional spatially collocated polarised antenna. Moreover, the DOA estimation accuracy can be improved greatly due to the extended aperture offered by sparse array. Computer simulation results verify the effectiveness of the proposed algorithm.